High intratumoural galectin‐1 expression predicts adverse outcome in ALK− ALCL and CD30+ PTCL‐NOS. Issue 1 (1st January 2020) - Holst, Johanne Marie; Ludvigsen, Maja; Hamilton‐Dutoit, Stephen Jacques; Bendix, Knud; Plesner, Trine Lindhardt; Nørgaard, Peter; Møller, Michael B.; Steiniche, Torben; Rabinovich, Gabriel A.; d'Amore, Francesco; Pedersen, Martin Bjerregård
Abstract: Galectin‐1 (Gal‐1) has been associated with adverse prognosis in several cancers including lymphoma entities with CD30 expression. However, Gal‐1 expression has not been systematically assessed in peripheral T‐cell lymphomas (PTCL). Specimens from 169 nodal PTCL were assessed for intratumoural Gal‐1 expression by immunohistochemistry. Overall survival (OS) in groups exhibiting high and low Gal‐1 expression was compared in the cohort and in a subset analysis of CD30‐positive PTCL only. Gal‐1 expression was also correlated with biomarkers of the tumour microenvironment. No significant difference in OS based on Gal‐1 expression was observed in the entire PTCL cohort. However, in the CD30‐positive cohort, patients with high Gal‐1 levels had significantly poorer outcome (5 years OS 10%, 95% confidence interval CI, 1‐36) than their low Gal‐1 counterparts (5 years OS 48%, 95% CI, 30‐64, P = .021). In univariate analyses age 60 or younger, non‐elevated lactate dehydrogenase (LDH), and performance score less than 2 correlated with superior survival but high Gal‐1 expression significantly predicted adverse outcome at both univariate (HR 2.5, 95% CI, 1.1‐5.7, P = .026) and multivariate levels (HR 3.2, 95% CI, 1.2‐8.5, P = .017). Tumours with high Gal‐1 had few cytotoxic T cells in the tumour microenvironment. High intratumoural Gal‐1 expression before therapeutic intervention correlates with adverse outcome in nodal CD30 +, ALK − PTCL patients.